2010
DOI: 10.1111/j.1365-3040.2009.02112.x
|View full text |Cite
|
Sign up to set email alerts
|

Do photosynthetic limitations of evergreen Quercus ilex leaves change with long‐term increased drought severity?

Abstract: Seasonal drought can severely impact leaf photosynthetic capacity. This is particularly important for Mediterranean forests, where precipitation is expected to decrease as a consequence of climate change. Impacts of increased drought on the photosynthetic capacity of the evergreen Quercus ilex were studied for two years in a mature forest submitted to long-term throughfall exclusion. Gas exchange and chlorophyll fluorescence were measured on two successive leaf cohorts in a control and a dry plot. Exclusion si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
116
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(134 citation statements)
references
References 63 publications
17
116
0
1
Order By: Relevance
“…Most studies show that decreases in soil moisture also reduce N and/or P uptake by plants (Jupp and Newman, 1987;Sardans and Peñuelas, 2007;Cramer et al, 2009;Waraich et al, 2011), suggesting a negative feedback of less water and fewer nutrients on the production capacity and fitness of plants when drought persists or becomes more severe. As a result, plants under drought tend to produce leaves and litter with high C-nutrient ratios (Yarie and Vancleve, 1996;Sardans et al, 2008b;Limousin et al, 2010). The few studies of the specific effects of drought on the N-P ratio in plants, however, have not provided a clear conclusion (Sardans and Peñuelas, 2008;Sardans et al, 2008c, in spite of studies in gradients of water availability in Mediterranean regions that have observed a negative correlation between water supply and leaf N-P ratio (Sardans et al, 2011), an effect linked to higher growth capacity in plants with lower N-P ratios .…”
Section: Drought Shifts In Elemental Compositionmentioning
confidence: 99%
“…Most studies show that decreases in soil moisture also reduce N and/or P uptake by plants (Jupp and Newman, 1987;Sardans and Peñuelas, 2007;Cramer et al, 2009;Waraich et al, 2011), suggesting a negative feedback of less water and fewer nutrients on the production capacity and fitness of plants when drought persists or becomes more severe. As a result, plants under drought tend to produce leaves and litter with high C-nutrient ratios (Yarie and Vancleve, 1996;Sardans et al, 2008b;Limousin et al, 2010). The few studies of the specific effects of drought on the N-P ratio in plants, however, have not provided a clear conclusion (Sardans and Peñuelas, 2008;Sardans et al, 2008c, in spite of studies in gradients of water availability in Mediterranean regions that have observed a negative correlation between water supply and leaf N-P ratio (Sardans et al, 2011), an effect linked to higher growth capacity in plants with lower N-P ratios .…”
Section: Drought Shifts In Elemental Compositionmentioning
confidence: 99%
“…a shift towards fewer and larger rainfall events, have received less attention; results have so far been inconclusive (Jentsch et al, 2007). Almost all experimental field studies manipulating rainfall amount or distribution have been conducted on annual plant communities or perennial grasslands Miranda et al, 2009), because of the difficulty of performing manipulation experiments on taller canopies (exceptions include Volder et al, 2010;Limousin et al, 2010;Misson et al, 2010). Despite the potential impact of changes in temporal patterns of rainfall distribution on shrublands and forests, data for these ecosystems is sparse.…”
Section: Introductionmentioning
confidence: 99%
“…Water stress caused by lower amounts of soil moisture thus clearly entailed a decrease in the soil-plant-atmosphere water flow (transpiration), shortly after the treatment had commenced (Limousin et al 2009), showing a rapid acclimation of plant funtioning to the new drier conditions. The consistent decrease in total transpiration was not accompanied by significant modifications of foliar gas exchange, neither the short term (after 1-4 years of drought treatment (Limousin, Misson, et al 2010;Ogaya, Llusià, et al 2014), nor the long term (after 14 years (Ogaya, Llusià, et al 2014;Sperlich et al 2015), indicating physiological homeostasis (Martin-Stpaul et al 2013). It should be noted, however, that measurements of leaflevel gas exchange are instantaneous.…”
Section: Trends Of Crown Defoliation and Their Relationship With Droumentioning
confidence: 84%
“…Both experimental designs excluded throughfall over ca. 30% of the plot surface (Limousin, Misson, et al 2010), and run-off at the Prades site was intercepted by ditches along the top edges of the plots . These experiments have produced a large body of information on the responses of Q. ilex forests to imposed moderate but continuous drought, from leaf-level physiology to ecosystem-level demography and fluxes of energy and matter.…”
Section: Trends Of Crown Defoliation and Their Relationship With Droumentioning
confidence: 99%
See 1 more Smart Citation